Literary Drama, Literacy and the Quest for Democracy in Nigeria: An Appraisal - Adeoti, Gbemisola Remi (2014)
This paper, therefore, appraises Nigeria's literary engagement in drama with the democratic imperative. Specifically, it discusses the genre's efforts at information (especially political) dissemination –a cardinal goal of literacy toward democratic changes. The discussion is done within the context of a perceived convergence of interest in the interface of literacy, drama and democracy.